Graphical Information and Classroom Booking System (GICBS) / Muhamad Sharmeeze Basar - Basar, Muhamad Sharmeeze (2012)
Nowadays, there are many systems and application has been migrated to the web-based in world. For the time being, in Fakulti Sains Komputer dan Matematik (FSKM), lecturers have difficulty to book a classroom using the current system. Lecturers have to open two different systems which are ICRESS scheduling system and FSKM Classroom Booking System for classroom booking process. Furthermore, classroom booking for students in FSKM is done by manually at the facility unit. This system is mainly to help students and lecturers to book a classroom in easiest ways. It is also to help administrator of FSKM to manage those classroom booking in more proper and systematic ways. Administrators do not have to key in the details of classroom booking made by students again. These systems no longer use the current manual form. All classrooms booking process is online web-based system. The aim of this system is to design a system which can combine classroom scheduling system and classroom booking system. With this system, students and lecturers can use the system in easily, save time and systematic compared to existed system. This system mainly focuses around FSKM at UiTM Shah Alam only. PHP language and MySQL database are used as the platform in development of this. Four major activities are being taken to completing the objectives of the system. The first activity is initial and planning to identify research area, problem statement, objectives, scope and significant of research. The second activity is requirement and analysis where data collection from the journals that are found. The third activity is designing system design and detailed design. The fourth activity is to develop Graphical Information and Classroom Booking System (GICBS). This completed system have make the classroom booking process easiest for students and lecturers also have a benefit to administrator in order to manage the system.